Bakhtiniana. Uma revista de estudos do discurso - Brait, Beth; Pistori, Maria Helena Cruz; Lopes-Dugnani, Bruna; Stella, Paulo Rogério; Gontijo Rosa, Carlos (Bakhtiniana. Revista de Estudos do Discurso, 2021)
Editorial 16.3